G2 Research Radically Invasive Projectile: The Importance of Recognizing Its Imaging and Autopsy Patterns. (September 2021) - Zhang, Xin; Cain, Matthew D.; Williams, Christian D.; Spears, Timothy A.; Poulos, Christopher K.
Abstract : Abstract: Many fragmenting and frangible projectiles have been developed in the course of firearm history. In addition, partially because of the concerns of range and environmental contamination, bullets constructed without lead have become increasingly common. A case regarding a unique projectile that incorporates both features, the G2 Research Radically Invasive Projectile ammunition, is discussed in this article. Here we report a 25-year-old woman who died of multiple gunshot wounds caused by G2 Research Radically Invasive Projectile ammunition. Because of the bullet's unique design, the wounds demonstrated characteristic radiographic patterns and unique autopsy findings. Familiarity with these findings is important to forensic pathologists in terms of case documentation, projectile recovery, and personal safety.